(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence and associated factors of dementia among patients after stroke at Can Tho Traditional Medicine Hospital in 2024. Methods: A cross-sectional descriptive study was conducted on 115 inpatients who had experienced a stroke at least three months prior, at Can Tho Traditional Medicine Hospital from June 2024 to October 2024. Results: Patients aged 60–80 years accounted for the majority of the sample (57.4%), with a slightly higher proportion of males (53.9%) compared to females (46.1%). Patients with a family history of stroke had a higher prevalence of dementia than those without such history (71.4% vs. 43.6%; p > 0.05). Three factors showed statistically significant associations with post-stroke dementia: obesity, cardiovascular disease, and diabetes mellitus. Conclusion: The prevalence of dementia among post-stroke patients was 48.7%. Factors associated with post-stroke dementia included obesity, cardiovascular disease, and diabetes mellitus. These findings highlight the necessity of proactive monitoring and cognitive screening in post-stroke patients with metabolic or cardiovascular comorbidities.